Factors affecting the invasion success of Senecio inaequidens and S. pterophorus in Mediterranean plant communities (Journal of Vegetation Science, 2007)
Question: Plant invasions result from complex interactions between species traits, community characteristics and environmental variations. We examined the effect of these interactions on the invasion potential of two invasive Senecio species, S. inaequidens and S. pterophorus, across three Mediterranean plant communities in a natural park. Location: Catalonia, NE Spain. Methods: We carried out two series of experimental seedling transplantations, in the spring and fall of 2003, in grassland, shrubland and Quercus ilex forest. Competition with neighbouring plants and water availability were manipulated. We evaluated the survival, growth and reproduction with respect to each treatment combination. Results: Any habitat can be colonised if disturbance occurs. In the absence of disturbance, shrubland enhanced the survival of seedlings. Competition with resident vegetation dramatically reduced survival in grassland and forest when establishment occurred in the spring. However, establishment in the fall promoted invasion in grassland and shrubland, even in the undisturbed treatment. Grassland allowed the highest growth and reproductive performance of both species while forest was the most resistant habitat to invasion. S. inaequidens had a higher growth rate and a shorter pre-reproductive period than S. pterophorus. S. pterophorus produced more biomass and was more dependent on water availability than S. inaequidens. Conclusions: In the light of our results, we recommend surveying open shrublands and grasslands after periods of rainfall. Special attention should be paid to S. pterophorus, which is currently spreading. A preliminary assessment of the invasive-ness of this plant is given in this study.

Methods of studing canopy cover of Quercus-ilex coppices (ACTA OECOLOGICA-OECOLOGIA APPLICATA, 1982)
APS